Analisis Program Ketakhassusan dalam Meningkatkan Sikap Religius dan Disiplin Siswa SMK Takhassus Al-Qur’an Kalibeber Wonosobo - Wahidah, Farkha Alfiyanti; Hamzah, Muchotob; Faisal, Vava Imam Agus (IIQ An Nur Yogyakarta, 2024)
The aim of this research was to find out how students were doing in improving religious attitudes and discipline at Takhassus Al-Qur'an Vocational School Wonosobo, how the implementation of the takhassus program was in improving students' religious attitudes and discipline, and what were the inhibiting and supporting factors for the takhassus Al-Qur'an program in improving attitudes toward religious and disciplined vocational school students. Researchers used a descriptive approach with a type of field research. The research subject was a purposive sampling technique, while the data collection techniques were observation, interviews and documentation. The results of this research concluded that the condition of students at Takhassus Al-Qur'an Vocational School in participating in the Takhassus Al-Qur'an program was quite good. Meanwhile, the implementation of the takhassus program could improve students' religious attitudes and discipline through habituation. Not only that, the inhibiting factor for takhassus program was that there were still many students who were lazy, while the supporting factor was that there were many Islamic boarding schools around the school, so they could support the program.